Relação humano-pet: significados e reflexos no cotidiano - Alencar, Ana Vitória Assunção Capistrano de (2022)
This study is based on the contemporary relationship established between humans and pets. The research aims to understand how the relationship between tutors and their pets is established, and how this relationship is reflected in different spheres of life. A variety of studies that explore the human-pet relationship in the field of consumer behavior are used as a basis for the literature. The qualitative approach is chosen, data collection takes place through the application of semi structured interviews using the snowball technique, carried out with 12 pet tutors. And how they are made from a content analysis aiming at the creation of five thematic categories: the contact with pets throughout life; process of arrival, adaptation and influence of pets in the routine; relationship between species and family interaction; the number of animals and their implications; and the tutor’s role considering their habits, rituals and restrictions. And in the identification of four functions performed by tutors: complacency, mediation, provision and protection. The research was limited to the behaviors identified only in the sample of participants, proposes the approach of companies regarding strategies to fidelize tutors in terms of the number of pets they have, and suggests that new approaches consider deepening the analysis of the mentioned functions and discovering other tutor’s roles in the lives of their pets.